Implementation of fiqh based on the maslahah in murabahah financing in sharia banking - Abdul Atsar; Azid Izuddin (State Institute of Islamic Studies (IAIN) Salatiga, 2018)
The law of Muamalat gives the freedom to bind themselves to contracts and conduct transactions for mutual benefits and benefits. Islamic banking prepares various types of contracts in accordance with sharia provisions, one of the murabahah contracts. The formulation of the problem in this study is how is the application of fiqh maslahah in Islamic banking murabahah financing contracts? The method used in this study is a normative juridical method, which refers to the concept of law as a rule. In this research the author of the legal approach, analytical approach. The specification of this study is descriptive analytical research. The type of data used in this study are secondary data and primary data. Data collection begins with activities to identify and inventory data sources. Drawing conclusions is done using inductive methods. Murabahah is a sale and purchase agreement between a bank and a customer where the bank buys the goods needed and resells the customer with a basic cost plus profits agreed by both parties, there is no coercion from the parties in making murabahah agreements. In making and implementing murabahah financing contracts must pay attention to public interests not just the interests of the parties. According to Islamic law in making contracts based on sharia principles, must prioritize the benefit and refuse harm to achieve the goal of shara, namely to increase the benefit of the people by guaranteeing basic needs (dharuriyah) and fulfilling secondary needs, needs (hajjiiyah) and their complementary needs.